INTRA-UTERIN ADMINISTRATION OF PROSTAGLANDIN FOR INDUCTION IN CROSS BREEDING GOATS - Sri Gustari; Asmarani Kusumawati; Slamet Subagyo; Prabowo P Putro (Jurnal Sain Veteriner, 1996)
Productivity and reproductivity of cross breeding goats is low. It is mainly caused by hormone deficiency and difficulties in estrus detection. The research studied the effect of intrauterine administration of prostagiandin on estrus induction and on number of pregnancies.Sixteen does were divided randomly into 2 groups. Group i were injected with prostagiandin intramuscularly. Group li were given prostagiandin by intrauterine administration. In both groups, prostagiandin were given twice with interval 11 days apart. The does which coming into estrus were mated naturally.There was a significantly different in the time of estrus between group I and group II (40.25 ± 4.94 and 80.8 ± 18.35 hours). On the other hand, there was no difference in estrus induction between those two groups (Group I : 87.5% and Group II : 62.5 %). All the does which were mated naturally were pregnant (100%). Although time to estrus after intrauterine administration of prostagfandin was longer than that of intramuscular ones, but it was a cheaper method.